Mitogen-Induced Interferon Gamma Production in Human Whole Blood: The Effect of Heat and Cations - Nam, Ji-Hyun; Cha, Bomi; Park, Jun-Young; Abekura, Fukushi; Kim, Cheorl-Ho; Kim, Jeong-Ran (Current Pharmaceutical Biotechnology, 2019)
Background: Interferon-gamma release assays (IGRAs) are blood tests used to measure the amount of interferon-γ (IFN-γ) released by T lymphocytes after stimulation by antigens specific for the diagnosis of latent tuberculosis infection. A mitogen serves as a positive control to assess the immune function in IGRAs. Methods: This in vitro study was conducted to evaluate IFN-γ production by human whole blood stimulated with heat-treated and/or cation-supplemented phytohemagglutinin (PHA), concanavalin A (Con A) and pokeweed mitogen (PWM), using QuantiFERON-TB Gold Kit ELISA tests. Results: The optimal concentrations of PWM, Con A and PHA for IGRAs were 2 μg/mL, 5 μg/mL and 10 μg/mL, respectively. The results showed that IFN-γ production in response to PWM was the highest and PHA was the lowest amount. The median values of three mitogens were in the following order: PWM≥Con A≥ positive control>>PHA-P>>negative control. PWM and PHA were heat stable, while Con A was heat sensitive. The mitogen response of lymphocytes to untreated or heat-treated PWM and heat-treated Con A was increased in 1 mM Ca2+-supplemented groups, whereas the response to heat-treated PHA was decreased. Exposure to 1 mM Mg2+ had no effect on untreated or heat-treated PWM, and a concentration of 1 mM Zn2+ inhibited the stimulation of un-treated PWM. We found that calcium supplementation improved the PWM-induced production of IFN-γ. Conclusion: Therefore, PWM is an appropriate mitogen for use as a positive control in IGRAs. It is a potential indicator of cytokine production in the diagnostic as well as research settings, and calcium supplementation improved stimulation.
Keywords: zinc